2023
DOI: 10.1101/2023.02.18.528972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biomimetic multi-channel microstimulation of somatosensory cortex conveys high resolution force feedback for bionic hands

Abstract: Manual interactions with objects are supported by tactile signals from the hand. This tactile feedback can be restored in brain-controlled bionic hands via intracortical microstimulation (ICMS) of somatosensory cortex (S1). In ICMS-based tactile feedback, contact force can be signaled by modulating the stimulation intensity based on the output of force sensors on the bionic hand, which in turn modulates the perceived magnitude of the sensation. In the present study, we gauged the dynamic range and precision of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 38 publications
(60 reference statements)
0
27
0
Order By: Relevance
“…Improved tactile discriminability and localizability has also been documented with the use of mICMS 2,14 . Moreover, mICMS can be used to provide a wider dynamic range of sensations, which can, for example, convey more levels of force 2 . However, a potential drawback of mICMS is its effect on motor decoding; S1 ICMS directly generates M1 activity 57 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Improved tactile discriminability and localizability has also been documented with the use of mICMS 2,14 . Moreover, mICMS can be used to provide a wider dynamic range of sensations, which can, for example, convey more levels of force 2 . However, a potential drawback of mICMS is its effect on motor decoding; S1 ICMS directly generates M1 activity 57 .…”
Section: Discussionmentioning
confidence: 93%
“…During stereognosis, both the cutaneous sense and the kinesthetic sense (input from receptors located in muscles, tendons, and joints) convey useful integrated information 52 . Previous studies have attempted to restore a sense of object shape, compliance or size using electrical stimulation of nerves 53,54 and cortex 2,55 . However, three-dimensional shape encoding that leverages tactile features on multiple digits has not been previously explored.…”
Section: Discussionmentioning
confidence: 99%
“…GS generally preserves neural spike-timing, respects on-going network activity, and maintains population firing rate distributions. Recent work has shown that more naturalistic, 'biomimetic' intracranial microstimulation (ICMS) outperforms traditional ICMS in somatosensory prosthesis for bionic hands [41]. Since GS mimics the natural cortical firing patterns more closely than PS, we expect it would be a good candidate for improving somatosensory prosthesis, along with any other ICMS application in which ongoing cortical network activity proves to be important.…”
Section: Discussionmentioning
confidence: 99%
“…Sombeck et al explored the decrease in neural activity by changing stimulation intensity from 5 to 100 µA and found that such depression duration and fraction of depressed neurons increased along with stimulation intensity increase [94]. These previous results suggest that, at least within the range used in prosthetic systems [95], greater stimulation pulse intensity drives both excitatory and inhibitory neurons more in terms of response magnitude and number of cells recruited [93]. This is different from what we observed in the current study by increasing stimulation frequency (figures 5 and 11) even though both greater stimulation pulse intensity and more frequent stimulation inject greater total charge into the cortex.…”
Section: Effect Of Stimulation Pulse Intensitymentioning
confidence: 95%